Gaya Kepemimpinan Transformasional, Kompetensi dan Tingkat Kepuasan Kerja terhadap Kinerja Karyawan PT. Serlok Kopi Surabaya - Krido Hery Gunawan; Sefia Eka Saputri (CiDEA Journal, 2024)
This research aims to prove and analyze the influence of transformational leadership, competency and level of job satisfaction on the performance of employees Serlok Kopi Surabaya partially or simultaneously. The population in this study was 55 respondents or all Serlok Kopi Surabaya employees. This research uses a sampling technique, namely a saturated sample using a data collection method through distributing questionnaires using quantitative data types. The method in this research uses the Validity Test, Reliability Test and Classical Assumption Test, data analysis is carried out using Multiple Linear Regression Analysis, while the hypothesis testing technique uses the t test and F test. Data analysis in this research uses SPSS version 25. The results of this research show that the variables Transformational Leadership (X1), Competency (X2), and ), Level of Job Satisfaction (X3) have a significant effect on employees Serlok Kopi Surabaya either partially or simultaneously.